أثر طريقة الصورة بالصورة على تنمية مهارة الكلام لدى الطلاب بالمدرسة الثانوية الثانية ستوبوندو - Wilda Fitria Yakin; Muhammad Alfan; Fahim Aghna 'lzzil Haq (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
Learning is an activity carried out by educators and learners in an environment that aims to achieve a learning goal. The fact is that in schools, there are still many educators who still need to achieve learning goals, especially learning maharah kalam. Therefore, the problem in schools is the low value of students in learning maharah kalam. This is due to an educator's need for more initiative in using several components that support the achievement of learning goals. One of these components is the learning method. Thus, the researchers used the picture-and-picture Learning method to develop students' Maharah Kalam. This study aimed to determine how the picture and picture method has influenced the development of Arabic speaking skills among students in MAN 2 Situbondo. In this study, researchers used quantitative approaches and types of experiments. This study's experiments and data collection methods use tests, questionnaires, observation, and documentary. Analysis of the data using the formula of the product of moments: r = nΣxy – (Σx)(Σy) /√nΣx² – (Σx)² nΣy2 – (Σy)2. The results of this study showed that the effect of the picture-and-picture method on the development of students ' speaking skills at an error rate of 5% is powerful. The average test result in the experimental class was 86.7, and in the observation class, 69.9. The data analysis results for the t-test calculation are 8.71 and T-schedule 1.67 or 8.71>1.67.